9/11 - Naudet, Jules; Naudet, Gedeon, 1970-; Hanlon, James, 1966-; Barber, Richard; La Rosa, Paul.; Paisley, Ian P.; Forman, Tom, 1893-1926.; Kandra, Greg.; Bryn, John.; Fuhr, Ken.; Furmanski, Jonathan; Goldstein, Jill.; et al. (Hollywood, Calif. : Paramount Pictures, 2002)
On the morning of September 11, 2001, brothers Jules and Gedeon Naudet were working on a documentary about a rookie New York City firefighter. Hearing a roar in the sky, Jules turned his camera upward--just in time to film the only existing image of the first plane crashing into the World Trade Center Tower 1. With cameras rolling, the Naudets follow NYC firefighters into the heart of what would be known as Ground Zero. A striking tribute to real-life heroes who rose to extraordinary acts of courage and compassion.
DVD, stereo.
Closed-captioned in English for the hearing impaired.
The firefighters from Engine 7, Ladder 1, Battalion 1.
Cinematographers, Jules Naudet, Gedeon Naudet, John Bryn, Ken Fuhr, Jonathan Furmanski, Jill Goldstein, Henry Olko, Aaron Tomlinson ; editor, Jason Schmidt ; original music score, Richard Fiocca.
Originally broadcast on CBS.
MPAA rating: Not rated.
Keywords: September 11 Terrorist Attacks, 2001.; Fire fighters -- New York (State) -- New York; World Trade Center (New York, N.Y. : 1970-2001); Terrorism -- New York (State) -- New York; Feature films; Video recordings; Documentary films; Video recordings for hard of hearing people